2007
DOI: 10.1149/1.2426409
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Between Nanocrystalline Host and Eu[sup 3+] Ions in GaN:Eu[sup 3+] Powders

Abstract: GaN nanocrystalline grains of diameter ϳ8 nm doped by Eu 3+ ions have been synthesized in the powder technology. The energy transfer between nanocrystalline GaN host and Eu 3+ ions has been investigated by photoluminescence excitation spectroscopy. It has been shown that there are three channels for the excitation of Eu 3+ ions: ͑i͒ through quantized states in GaN nanocrystals, ͑ii͒ through defect-related states in the GaN, and ͑iii͒ directly through the excited states of Eu +3 ions. It has been found that for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In our recent work [10] it has been shown that there are different excitation channels for the europium ions doped into GaN nanoparticles: indirect (excitation below 360 nm) and direct ones. As it can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work [10] it has been shown that there are different excitation channels for the europium ions doped into GaN nanoparticles: indirect (excitation below 360 nm) and direct ones. As it can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, other, energetically lower absorption transitions are possible, namely 4f Eu → ͑3d Ti͒ CB , and local excitation of Eu 3+ ions at the surface, i.e., ͑2p O͒ → 4f Eu, where a hole is left behind on nearby ligands. 35,36 In consequence, the absorption edge should even be redshifted. 37 This is not the case, probably due to the small eu- ropium concentration ͑0.1%͒, while other authors, for Nd 3+ ions, have observed this effect for much higher dopant concentrations ͑ϳ1.5%͒.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, relatively to NCRE volume, more RE ions are present at the surface and surface effect start to play an important role. Since these ions are in different local environment than core sites, changes in optical properties of the marker can be observed [6].…”
Section: Introductionmentioning
confidence: 99%